Pengaruh Pelatihan Coaching terhadap Kemampuan Pemecahan Masalah pada Supervisor - Dian Dwi Nur Rahmah; Arief Fahmie (Universitas Islam Indonesia, 2016)
This study aims to determine the effectiveness of coaching training in improving problem solving skills of PT.X supervisor in East Kalimantan. The hypothesis is that coaching training could enhance the ability of problem solving of supervisor. Coaching consists of four aspects, there are able to understand the problem, able to seek and assess alternative solutions, able to implement the solution, and able to carry out an evaluation of the solutions that have been implemented. The study involved 26 new supervisors with tenure 1-3 years. Measuring instrument was problem solving scale (Ellis and Hunt, 1993), which had 25 items. Data analysis using independent sample t-test showed a nonsignificance value of p value (p = 0.506> 0.05) in the post-test, the hypothesis stated are not accepted. Thus, there is no difference in the ability of solving problems in experimental and control groups. However, when the implementation of the follow-up showed a significance value p value (p = 0.030> 0.05), which indicates that there are differences in post-test to follow up of the experimental group.Â Keywords: coaching training, problem solving ability